Targeting ferroptosis: a new therapeutic opportunity for kidney diseases - Long, Zhiyong; Luo, Yanfang; Yu, Min; Wang, Xiaoyan; Zeng, Liuting; Yang, Kailin (Frontiers in Immunology, 2024)
Ferroptosis is a form of non-apoptotic regulated cell death (RCD) that depends on iron and is characterized by the accumulation of lipid peroxides to lethal levels. Ferroptosis involves multiple pathways including redox balance, iron regulation, mitochondrial function, and amino acid, lipid, and glycometabolism. Furthermore, various disease-related signaling pathways also play a role in regulating the process of iron oxidation. In recent years, with the emergence of the concept of ferroptosis and the in-depth study of its mechanisms, ferroptosis is closely associated with various biological conditions related to kidney diseases, including kidney organ development, aging, immunity, and cancer. This article reviews the development of the concept of ferroptosis, the mechanisms of ferroptosis (including GSH-GPX4, FSP1-CoQ1, DHODH-CoQ10, GCH1-BH4, and MBOAT1/2 pathways), and the latest research progress on its involvement in kidney diseases. It summarizes research on ferroptosis in kidney diseases within the frameworks of metabolism, reactive oxygen biology, and iron biology. The article introduces key regulatory factors and mechanisms of ferroptosis in kidney diseases, as well as important concepts and major open questions in ferroptosis and related natural compounds. It is hoped that in future research, further breakthroughs can be made in understanding the regulation mechanism of ferroptosis and utilizing ferroptosis to promote treatments for kidney diseases, such as acute kidney injury(AKI), chronic kidney disease (CKD), diabetic nephropathy(DN), and renal cell carcinoma. This paves the way for a new approach to research, prevent, and treat clinical kidney diseases.